Age has a U-shaped relationship with breast cancer outcomes in women: a cohort study - Xie, Yujie; Deng, Yongqing; Wei, Suosu; Huang, Zhen; Li, Lihui; Huang, Kai; Wei, Chunyu; Xu, Jinan; Dong, Lingguang; Zhang, Qiuhuan; Zhao, Jiehua; Zou, Quanqing; et al. (Frontiers in Oncology, 2023)
Background and Objectives Age is a significant determinant of susceptibility to breast cancer. Currently, the available evidence regarding the non-linear correlation between the age of diagnosis and the prognosis of breast cancer patients is contradictory. Insufficient data currently exist regarding the influence of age at diagnosis on the prognosis of breast cancer. The objective of our investigation was to examine the relationship between age at diagnosis and overall survival (OS), breast cancer-specific survival (BCSS), and disease-free survival (DFS). Methods This retrospective cohort study included 1054 patients diagnosed with breast cancer between March 7, 2013 and December 31, 2019. The hazard ratios (HRs) and 95% confidence interval (CI) for OS, BCSS, DFS were assessed using Cox proportional hazard ratio models and restricted cubic splines (RCS). Results The study included 1054 breast cancer patients who met the criteria. With a median follow-up of 4.86 years, 71 patients (6.74%) died and 144 patients (13.66%) relapsed. After multivariable adjustment, age showed a U-shaped association with OS, BCSS, and DFS, with significantly higher risk at two ends, with age inflection points of 44, 44, and 41 years for OS, BCSS, and DFS, respectively. For OS, Quartile 1 (HR, 2.09; 95% CI: 0.90-4.84), Quartile 3 (HR, 2.44; 95% CI: 1.05-5.65) and Quartile 4 (HR, 3.38; 95% CI: 1.51-7.54) had poorer OS compared with Quartile 2. Similar results were found for BCSS and DFS. Conclusions This study confirmed a U-shaped association between age at diagnosis and breast cancer outcome.